2021
DOI: 10.1016/j.ctro.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Development and internal validation of multivariable prediction models for biochemical failure after MRI-guided focal salvage high-dose-rate brachytherapy for radiorecurrent prostate cancer

Abstract: Background and purpose: Magnetic resonance-guided focal salvage high-dose-rate brachytherapy (FS-HDR-BT) for radiorecurrent prostate cancer (PCa) shows low toxicity rates. However, biochemical failure (BF) after treatment occurs frequently. We developed two prediction models for BF (Phoenix definition) with the aim of enhancing patient counselling before FS-HDR-BT and during follow-up. Materials and methods: A prospective cohort of 150 radiorecurrent PCa patients treated with FS-HDR-BT between 2013 and 2020 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…There exists one other published model by Willigenburg et al. [20] in the setting of salvage focal brachytherapy, but this has not been externally validated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There exists one other published model by Willigenburg et al. [20] in the setting of salvage focal brachytherapy, but this has not been externally validated.…”
Section: Discussionmentioning
confidence: 99%
“…It will be useful to evaluate how novel radiological parameters may improve models. Between the models by Peters et al [7] and Willigenburg et al [20], radiological variables considered were prostate volume, lesion volume, and stage. However, these do not necessarily quantify the likelihood of radiorecurrent disease.…”
Section: Future Directionsmentioning
confidence: 99%
“…The association between Gleason score and outcome after focal salvage is not clear: some studies find a correlation [53], but other studies do not [54,55]. Prediction models with a good performance are available, also in the setting of focal salvage HDR brachytherapy [56], in which other parameters have been described to be predictive of biochemical failure after focal salvage HDR brachytherapy for locally recurrent prostate cancer, such as gross tumor volume, pre-salvage PSA-value, and pre-salvage PSA doubling time [56]. Gleason score seems to be of limited added value, due to the inconclusive findings in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…For patients treated with salvage treatment, two studies reported on outcomes with 2-year PSA control rates ranging from 42% to 59%. These results, similar to the definitive setting, demonstrated less than ideal outcomes with single-fraction treatment [ 12 , 16 ].…”
Section: Prostatementioning
confidence: 92%
“…Eight studies treated patients with androgen deprivation therapy treatment over a range between 3 and 36 months. In the definitive therapy series, median follow-up ranged from 20 to 72 months, while in the salvage series it ranged from 25 to 26 months [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Clinical Outcomesmentioning
confidence: 99%